Transient multi-day simulations of thermal storage and heat extraction for a finned solar thermal storage device. (15th July 2017) - Augspurger, Mike; Udaykumar, H.S.
Highlights: 48-h long simulations of latent-heat thermal storage devices are performed. Four devices, each with a different aluminum finned heat spreader, are tested. Simulations cover two full diurnal cycles, and include heat charging and withdrawal. Devices are compared based on efficiency of charging and withdrawal processes. Fin design affects efficiency and convection flow patterns in complex manner. Abstract: The effect of combining metal fins (Al) for heat spreading and recovery with phase change material (a mixture of NaNO3 and KNO3 ) on the performance of a thermal storage device is investigated. High-resolution transient simulations are performed covering two days of solar energy influx and heat extraction. The solver uses the enthalpy method to track melting, a strongly coupled implicit scheme to calculate conjugate heat transfer, and a dynamically refined mesh to ease grid creation and maximize computational efficiency. A potential application is thermal storage for solar cooking, although other applications can also be envisaged. The energy inputs of the simulations are based average solar radiation during a 48 h solar cycle in New Delhi, India in June with a 1.5 m 2 solar reflector. Four different fin designs for an insulated latent heat thermal storage device (TSD) to be used with a solar cooker are tested. The four designs are compared based on their ability to spread heat evenly and rapidly into the phase change material (PCM) and the ease with which heat can be withdrawn from the device for cooking. The tests demonstrate the potential for using long term, multiday numerical simulations in the evaluation of TSD designs.